Analisis Keandalan Berbasis Sistem Pada Jaringan Distribusi 20kV UPJ PT. PLN Persero Area Pekanbaru Rayon Panam - Yusuf Ridho Surya Dharma Nainggolan; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The aim of this study was to calculate the index value the reliability of the system based on a network of 20 kV electrical power distribution at the feeder PT PLN (Persero) Rayon Panam, and compared with the value that has been targeted by PT. PLN (Persero) Rayon Panam in 2015. The study also aimed to determine the level of reliability of the system at each Feeder PT PLN (Persero) Rayon Panam. This research is descriptive, the object of this study is the Electricity Distribution Network at 20 kV feeder PT PLN (Persero) Rayon Panam. Data analysis technique using the equation according to a formula-based system reliability indices are SAIFI, SAIDI, CAIFI, CAIDI, ASAI and Asui. The results of this study indicate that the reliability index value based on Rayon Panam system is in the category unreliable. SAIFI reliability index value highest in Kualu feeder with a value of 13.33 disturbance / year and SAIFI reliability index was lowest for the feeder of Riau with a value of 3.5 disorder / year. Then on SAIDI reliability indices highest in Kualu feeder with a value of 12.63 hours / year and the lowest in Radish feeder and feeder Wildlife Works with a value of 5.86 hours / year. Keywords: SAIDI, SAIFI, CAIDI, CAIFI, ASAI and ASUI.